Investigação experimental da recirculação de gases de exaustão em um motor de combustão por centelha com atuação de válvula variável operando com gasolina e etanol - Heder Fernandes (2017)
Exhaust Gas Recirculation EGR is a well-known technique to reduce NOx and it has been applied on Diesel engines for a long time. Previous studies and application found that other benefits can be achieved with PFI and GDI gasoline engines, such as pumping loss minimization and efficient knock control. Variable valve actuation valve-trains brought broader application possibilities as it enables full internal EGR control without external paths, high precision and response, as required on transient work modes. This work involves investigating the effects of internal exhaust gas recirculation IEGR on the combustion, fuel economy and emissions of a variable valve actuation engine (FCA Multiair II) operating with gasoline and ethanol in a part-load condition. This technology allows to control and anticipate the intake valve opening angle in a wide range, increasing the overlap angle and consequently the IEGR flow, that is the amount of burned gas mass that has flowed from the cylinder across the intake valve into the intake runner during the exhaust phase. Two configurations of partial load control were studied with internal EGR. In Configuration 1 the fresh air mass is substituted by EGR mass and in Configuration 2 the burned gas is used to optimize the intake valve closing angle in an EIVC operation mode. In addition, a physical model was proposed to calculate the exhaust gas recirculated mass in the intake manifold. The results showed that Configuration 2 presents better fuel consumption values in relation to Configuration 1 up to 7% with ethanol and 4% with gasoline. The proposed model presented good qualitative results but was limited by the sampling frequency of the CO2 measurement in the intake manifold. It has been demonstrated that the use of internal EGR strategies with ethanol has great advantages over gasoline because it is a high knock resistance fuel, which is another benefit of the Brazilian energy matrix based on renewable fuels.